Improving the Quality of Islamic Education Management ThroughTotal Quality Management - Putri Syahri (Education Achievement: Journal of Science and Research, 2023)
Quality issues always have an impact on the selling power of educational institutions. The success and reputation of an institution depends heavily on the quality of teaching, infrastructure and facilities, support services, teachers and students, and learning outcomes. This study intends to show how to improve the quality of Islamic Education Management through Total Quality Management. The research method used is library research, where data is obtained from books, internet journals and all data that can meet research findings. After collecting, presenting and evaluating data, the quality of education is the process of learning, learning and learning outcomes. High quality education if it meets the needs of all parties, if all parties involved in education are of high quality such as human resources and all the supporting facilities and infrastructure for the education. In Islamic educational institutions, the main goal of TQM is to meet the needs of society. Excellent Islamic educational institutions will always maintain community ties and improve the quality of higher quality resources. By implementing TQM, the quality of education will be realized.